Penegakan Hukum Pidana Terhadap Perbuatan Cabul Bagi Mayat (Studi Putusan Nomor 62/PID.B/2020/PN.BNR) - Marasabessy, Santy; Hehanussa, Deassy Jacomina Anthoneta; Tuhumury, Carolina (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Obscene acts for corpses are very heinous and indecent. This action relates to the norms of decency, the honor of a person. The research method used is normative juridical using a statutory approach, a conceptual approach and a case approach. The legal materials used are primary, secondary, and tertiary legal materials. The analysis of the legal material used is qualitative analysis. The results showed that: in criminal law enforcement against lewd acts for corpses, the rule of law against the accused KIRAH ALIAS BOLOT PRIMARI. The defendant has been legally and conclusively proven guilty of murder and corpse molestation, therefore the author uses concursus in research as a thought and policy in following up the study of the verdict in this writing. In accordance with the facts of the trial that took place, according to the author, the sentence for the accused KIRAH must be toughened again in order to have a deterrent effect on the perpetrators.